APPLICATION OF TRECER METHODS AND HYDROCHEMICAL ANALYSIS ON THE KARST SYSTEM OF Ν . OSSA MOUNTAIN/NE -THESSALY - Σταμάτης, Γ.; Ζαγγανά, E. (Bulletin of the Geological Society of Greece, 2004)
In this paper the hydrogeological conditions of the north part of Ossa mountain are described. The research is focused on the karstic aquifer and the springs of its organic contamination are checked. Hydrochemical methods and tracer methods with NaCI and Uranine as tracers were applied. Regarding the inorganic chemical load, karstic waters show high quality status without any surface loading due to its dilution. Tracer tests reveal high groundwater flow velocity Va values ranging from 82 m/h to 146 m/h due to the intense karst and the existence of caves. Groundwater flow present NE direction and the discharge of karst aquifer take place in the Tempi value. The recorded contamination within the recharge area of the karstic springs is directly connected to anthropogenic impacts and incomplete water collection infrastructure. Actions for the aquifer protection must be taken the soonest possible.